Identifying the Start of Multiple Sclerosis Injury: A Serial DTI Study. Issue 6 (23rd February 2014) - Ontaneda, Daniel; Sakaie, Ken; Lin, Jian; Wang, Xiaofeng; Lowe, Mark J.; Phillips, Michael D.; Fox, Robert J.
ABSTRACT: BACKGROUND: The events leading up to the development of new multiple sclerosis (MS) lesions on conventional imaging are unknown. The purpose of this study is to use diffusion tensor imaging (DTI) to investigate prelesional changes in MS to better understand the pathological changes that lead to lesion development. METHODS: Twenty‐one patients with relapsing MS starting natalizumab therapy underwent serial DTI for 12‐18 months. Regions of interest were outlined within normal‐appearing white matter and new gadolinium‐enhancing lesions that developed over the course of the study. Images from all time points were coregistered and nonparametric regression was used to assess DTI changes prior to lesion appearance. RESULTS: A total of 31 newly enhancing lesions were identified. Significant changes in transverse diffusivity (TD) ( P < .001), longitudinal diffusivity (LD) ( P = .025), mean diffusivity (MD) ( P < .001), and fractional anisotropy (FA) ( P = .04) were observed prior to gadolinium enhancement. A progressive increase in TD and LD occurred up to 10 months prior to lesion development. DTI measures in normal appearing white matter remained unchanged over the study period. CONCLUSIONS: A significant change in diffusion measures can be seen prior to gadolinium enhancement. Changes in TD drove changes in FA and MD, providing evidence for impaired myelin integrity prior to gadolinium enhancement. DTI may be a sensitive measure for early detection of inflammatory disease activity in MS.